1981
DOI: 10.1007/bf00385534
|View full text |Cite
|
Sign up to set email alerts
|

Amino-acid transport into cultured tobacco cells

Abstract: Arginine transport in suspension-cultured cells of Nicotiana tabacum L. cv. Wisconsin-38 was investigated. Cells that were preincubated in the presence of Ca(2+) for 6 h prior to transport exhibited stimulated transport rates. After the preincubation treatment, initial rates of uptake were constant for at least 45 min. Arginine accumulated in the cells against a concentration gradient; this accumulation was not the result of exchange diffusion. Arginine uptake over a concentration range of 2.5 μM to 1 mM was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Some researchers who use tris buffers in their preincubation solutions have concluded that calcium is required in the preincubation solution in order to obtain uptake rate increases for amino acids (2,8,18). Others have reported that increases in uptake rate do not require the presence of calcium in the preincubation solution (11,15).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some researchers who use tris buffers in their preincubation solutions have concluded that calcium is required in the preincubation solution in order to obtain uptake rate increases for amino acids (2,8,18). Others have reported that increases in uptake rate do not require the presence of calcium in the preincubation solution (11,15).…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been observed using a number of species and for a broad range ofsubstrates: phosphate, potassium, chloride, glycine, glucose, and guanosine monophosphate (11); sulfate (10); L-serine (18); malate, glycerate-3-P, uracil, and several amino acids (8) (2,7,8,10,18). However, other researchers have demonstrated that an enhanced uptake rate can be induced without the addition of calcium to the preincubation solution (6,11,15).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations